2021
DOI: 10.7759/cureus.18431
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Antibiotic Use in Public Health Care Facilities of South Indian Union Territory: A Step to Promote Rational Use of Antibiotics

Abstract: IntroductionAntimicrobial resistance is a serious problem to solve for the public health authorities at the global level, particularly in developing countries like India. One of the possible reasons for antimicrobial resistance could be the inappropriate or overuse of antibiotics. The Indian government started the National Action Plan on Antimicrobial Resistance to promote rational use of antibiotics in our country. This study was conducted with the objective to monitor antibiotic use in public health faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…Similar to our finding, a study at nine primary healthcare facilities in India found ciprofloxacin to be the most prescribed Watch antibiotic. 36 Contrary to our findings, a study that assessed antibiotic overuse in primary healthcare settings revealed higher use of Watch antibiotics, mostly quinolones and cephalosporins, in China and India, with only Kenya mostly using Access antibiotics. 39 A study in rural Burkina Faso that assessed the use of Watch antibiotics before hospital presentation and another study in China that assessed antibiotic prescription patterns in 48 primary healthcare facilities both found ceftriaxone to be the most commonly prescribed, followed by ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to our finding, a study at nine primary healthcare facilities in India found ciprofloxacin to be the most prescribed Watch antibiotic. 36 Contrary to our findings, a study that assessed antibiotic overuse in primary healthcare settings revealed higher use of Watch antibiotics, mostly quinolones and cephalosporins, in China and India, with only Kenya mostly using Access antibiotics. 39 A study in rural Burkina Faso that assessed the use of Watch antibiotics before hospital presentation and another study in China that assessed antibiotic prescription patterns in 48 primary healthcare facilities both found ceftriaxone to be the most commonly prescribed, followed by ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 99%
“… 34 Penicillins were widely used in primary healthcare, with oral amoxicillin being the most commonly prescribed; comparable to our findings, a scoping review found amoxicillin to be the most commonly prescribed in East Africa, West Africa, New Zealand, Cuba and Brazil, 35 and India. 36 The overuse of penicillins in primary healthcare facilities could be attributed to the lack of facility-based treatment guidelines supported by local microbiology data. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The overuse and misuse of antibiotics have contributed to the increase bacterial resistance to the antibiotic 2 . A majority of patients receiving antibiotics in this district were predominantly male, consistent with another study done in South India 9 . Adherence and appropriateness of Cloxacillin prescriptions was low compared to the National Antibiotic guideline, similar with a study conducted in Kedah, Malaysia 2, 6 .…”
Section: Discussionsupporting
confidence: 90%
“…32,33 Our study reveals that majority (96.4%), would like to have more evidence-based therapy guidelines for antibiotic therapy with lesser limitations. 34,35 The participants read online scientific journals (78.2%) as a major information source on antibiotic therapy and resistance. 36…”
Section: Discussionmentioning
confidence: 99%